Canagliflozin-associated diabetic ketoacidosis: a case report. Issue 1 (1st January 2017) - Chai, Peter R.; Bonney, Caitlin; Blohm, Eike; Boyer, Edward W.; Babu, Kavita M.
ABSTRACT: Canagliflozin is a novel sodium-glucose cotransporter-2 (SGLT-2) inhibitor approved for the management of diabetes. We report the presentation and management of two cases of canagliflozin associated diabetic ketoacidosis (DKA) and discuss the mechanism of canagliflozin associated DKA. Patient 1, a 55 year old woman maintained on canagliflozin for diabetes mellitus II presented to the emergency department (ED) with 24 hours of nausea and vomiting. She was diagnosed with DKA featuring hypotension, hyperglycemia, ketosis and acidosis. A second 54 year old man also maintained on canagliflozin for diabetes mellitus I presented to the ED with 24 hours of nausea and vomiting. He was diagnosed with DKA with similar manifestations as patient 1. Both patients underwent massive volume resuscitation and intravenous insulin therapy with resolution of ketosis and acidosis. By inhibiting SGLT-2, canagliflozin promotes glucosuria, which in turn can produce up to a 10% decrease in total plasma volume rendering patients maintained on canagliflozin susceptible to dehydration. Inhibition of SGLT-2 also leads to glucagon secretion, which in the volume deplete individual, can exacerbate DKA. Physicians should be aware of the rapid onset of DKA in patients maintained on canagliflozin after just minor additional fluid losses.